2019
DOI: 10.1039/c9ra04727a
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence and energy transfer of Tm3+ and Dy3+ co-doped Na3ScSi2O7 phosphors

Abstract: A series of Tm3+ and Dy3+ ions single- or co-doped Na3ScSi2O7 (NSSO) phosphors were prepared by a conventional solid state reaction method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 27 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Then, we measured the PLQY ( η ) of Ca 2 LaHf 2 Al 3 O 12 :50%Eu 3+ phosphors using the following formula herein L S stands for the sample’s emission spectrum and E S denotes the excitation spectrum with the Ca 2 LaHf 2 Al 3 O 12 :50%Eu 3+ phosphor, while E R represents the excitation spectrum without the Ca 2 LaHf 2 Al 3 O 12 :50%Eu 3+ phosphor. The obtained PLQY value of 64% for the Ca 2 LaHf 2 Al 3 O 12 :50%Eu 3+ phosphor is superior to that for several red phosphors including Li 3 Y 3 Te 2 O 12 :Eu 3+ (PLQY = 61%), Y 2 Mg 2 Al 2 Si 2 O 12 :Eu 3+ (PLQY = 60.5%), Li 6 CaLa 2 Nb 2 O 12 :Eu 3+ (PLQY = 51%), Li 2 TiO 3 :Mn 4+ (PLQY = 31.6%), CaGdAlO 4 :Mn 4+ (PLQY = 45%), and Li 4 AlSbO 6 :Mn 4+ (PLQY = 54.8%) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we measured the PLQY ( η ) of Ca 2 LaHf 2 Al 3 O 12 :50%Eu 3+ phosphors using the following formula herein L S stands for the sample’s emission spectrum and E S denotes the excitation spectrum with the Ca 2 LaHf 2 Al 3 O 12 :50%Eu 3+ phosphor, while E R represents the excitation spectrum without the Ca 2 LaHf 2 Al 3 O 12 :50%Eu 3+ phosphor. The obtained PLQY value of 64% for the Ca 2 LaHf 2 Al 3 O 12 :50%Eu 3+ phosphor is superior to that for several red phosphors including Li 3 Y 3 Te 2 O 12 :Eu 3+ (PLQY = 61%), Y 2 Mg 2 Al 2 Si 2 O 12 :Eu 3+ (PLQY = 60.5%), Li 6 CaLa 2 Nb 2 O 12 :Eu 3+ (PLQY = 51%), Li 2 TiO 3 :Mn 4+ (PLQY = 31.6%), CaGdAlO 4 :Mn 4+ (PLQY = 45%), and Li 4 AlSbO 6 :Mn 4+ (PLQY = 54.8%) …”
Section: Resultsmentioning
confidence: 99%
“…Particularly, the color purity of optimal Ca 2 LaHf 2 Al 3 O 12 :50% Eu 3+ phosphors reached 92.7%, surpassing that of N a 3 S c 2 ( P O 4 ) 3 : E u 3 + ( c o l o r p u r i t y = 8 7 % ) , 6 9 Gd 3 Zn 2 Nb 3 O 14 :Eu 3+ (color purity = 91.2%), 70 Ca 2 SiO 4 :Eu 3+ (color purity = 91%), 71 and CaWO 4 :Eu 3+ (color purity = 91.3%). 72 Then, we measured the PLQY (η) of Ca 2 LaHf 2 Al 3 O 12 :50% Eu 3+ phosphors using the following formula 73 phosphor is superior to that for several red phosphors i n c l u d i n g L i 3 Y 3 T e 2 O 1 2 :E u 3 + ( P L Q Y = 6 1 % ) , 7 7 Y 2 M g 2 A l 2 S i 2 O 1 2 : E u 3 + ( P L Q Y = 6 0 . 5 % ) , 2 6 Li 6 CaLa 2 Nb 2 O 12 :Eu 3+ (PLQY = 51%), 78 Li 2 TiO 3 :Mn 4+ (PLQY = 31.6%), 79 CaGdAlO 4 :Mn 4+ (PLQY = 45%), 80 and Li 4 AlSbO 6 :Mn 4+ (PLQY = 54.8%).…”
Section: Morphology and Elementalmentioning
confidence: 99%
“…[21][22][23][24] Thulium doped inorganic phosphors could be also applicable in white light emitting diodes (wLEDs) through Dy 3+ co-doping. 25 Structural, thermal and optical properties of ceramics Li 2 -MgGeO 4 un-doped and doped with Er 3+ and Ho 3+ ions were described in our previous work. 26 Direct energy band gaps for Li 2 MgGeO 4 with Er 3+ and Ho 3+ are found to be 5.67 and 5.77 eV and they are comparable to the values reported earlier.…”
Section: Introductionmentioning
confidence: 99%
“…21–24 Thulium doped inorganic phosphors could be also applicable in white light emitting diodes (wLEDs) through Dy 3+ co-doping. 25…”
Section: Introductionmentioning
confidence: 99%
“…Zhong found that the excellent luminescent properties and thermal stability of blue phosphor KBaScSi 2 O 7 :Eu 2+ arised from the fact that Sc has better rigid environment . Take scandium silicate phosphors as an example, due to the abundant Sc environment and weak electron-acoustic coupling in the crystal structure, the phosphors have high luminous efficiency and good thermal stability. Therefore, the development of new silicic acid Sc phosphors with desired properties is important for basic research and application fields.…”
Section: Introductionmentioning
confidence: 99%